2019
DOI: 10.1007/s10815-019-01446-5
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of mural granulosa cells is increased in women with diminished ovarian reserve

Abstract: Purpose To evaluate the relationship between apoptosis of granulosa cells in women with normal ovarian reserve versus diminished ovarian reserve, and relate that to follicular fluid hormones, and to clinical outcomes. Methods A prospective cohort study was initiated between October 2015 and June 2016 involving a total of 164 women undergoing IVF/ICSI cycles at a single IVF center. Mural and cumulus granulosa cells, and follicularfluid were collected during oocyte retrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 39 publications
1
50
0
Order By: Relevance
“…The etiology and pathogenesis of DOR remain unclear so far, but it has been reported that DOR may be related to age (Fan et al, 2019), immunity (Silva et al, 2014), heredity, environment, radiotherapy and chemotherapy (Smith et al, 2013), surgery, psychological stress (Nicoloro-SantaBarbara et al, 2017), and infectious factors (Soylu Karapinar et al, 2017). A prospective cohort study found that poor ovarian response was related to age and apoptosis of ovarian granulosa cells (Fan et al, 2019). Hyperfunction of the autoimmune system might damage ovary through antigen-antibody reactions (Silva et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The etiology and pathogenesis of DOR remain unclear so far, but it has been reported that DOR may be related to age (Fan et al, 2019), immunity (Silva et al, 2014), heredity, environment, radiotherapy and chemotherapy (Smith et al, 2013), surgery, psychological stress (Nicoloro-SantaBarbara et al, 2017), and infectious factors (Soylu Karapinar et al, 2017). A prospective cohort study found that poor ovarian response was related to age and apoptosis of ovarian granulosa cells (Fan et al, 2019). Hyperfunction of the autoimmune system might damage ovary through antigen-antibody reactions (Silva et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The ovary is an important organ for follicle development and ovulation, and the development of the follicle is accompanied by the growth, development and differentiation of granulosa cells (8,9). The proliferation and apoptosis of ovarian granulosa cells was discovered to be closely associated with ovarian development (10,11), thus, ovarian granulosa cells are usually used to study the associated mechanisms of PCOS (12)(13)(14). For this reason, the present study also studied PCOS using ovarian granulosa cells.…”
Section: Introductionmentioning
confidence: 95%
“…Similarly, in the human model the majority of related studies have been focused on granulosa cells isolated from FF during oocyte collection. Apoptosis, evaluated by EP, of granulosa cells has been negatively associated to egg and embryo numbers in IVF/ICSI cycles, pregnancy rate and live birth rate after IVF [139,140]. But contrarily, it has been also reported that the EP in granulosa cells is not related to follicular quality and oocyte competence during ICSI [141].…”
Section: Cell Death (Apoptosis) In Cumulus Cellmentioning
confidence: 99%